Intranasal midazolam as first‐line inhospital treatment for status epilepticus: a pharmaco‐EEG cohort study. Issue 12 (4th November 2019) - Kay, Lara; Merkel, Nina; von Blomberg, Anemone; Willems, Laurent M.; Bauer, Sebastian; Reif, Philipp S.; Schubert‐Bast, Susanne; Rosenow, Felix; Strzelczyk, Adam
Abstract: Objective: We sought to evaluate the efficacy and tolerability of intranasal midazolam (in‐MDZ) as first‐line inhospital therapy in patients with status epilepticus (SE) during continuous EEG recording. Methods: Data on medical history, etiology and semiology of SE, anticonvulsive medication usage, efficacy and safety of in‐MDZ were retrospectively reviewed between 2015 and 2018. Time to end of SE regarding the administration of in‐MDZ and ß‐band effects were analyzed on EEG and with frequency analysis. Results: In total, 42 patients (mean age: 52.7 ± 22.7 years; 23 females) were treated with a median dose of 5 mg of in‐MDZ (range: 2.5–15 mg, mean: 6.4 mg, SD: 2.6) for SE. The majority of the patients suffered from nonconvulsive SE ( n = 24; 55.8%). In total, 24 (57.1%) patients were responders, as SE stopped following the administration of in‐MDZ without any other drugs being given. On average, SE ceased on EEG at 05:05 (minutes:seconds) after the application of in‐MDZ (median: 04:56; range: 00:29–14:53; SD:03:13). Frequency analysis showed an increased ß‐band on EEG after the application of in‐MDZ at 04:07 on average (median: 03:50; range: 02:20–05:40; SD: 01:09). Adverse events were recorded in six patients (14.3%), with nasal irritations present in five (11.9%) and prolonged sedation occurring in one (2.6%) patient. Conclusions: This pharmaco‐EEG–based study showed that in‐MDZ is effective and well‐tolerated for the acute treatment of SE. EEG and clinical effects of in‐MDZ administration occurred within 04:07 and 5:05 on average. Intranasal midazolam appears to be an easily applicable and rapidly effective alternative to buccal or intramuscular application as first‐line treatment if an intravenous route is not available.